TDP-43 and ER Stress in Neurodegeneration: Friends or Foes? - de Mena, Lorena; Lopez-Scarim, Joshua; Rincon-Limas, Diego E. (Frontiers in Molecular Neuroscience, 2021)
Nuclear depletion, abnormal modification, and cytoplasmic aggregation of TDP-43 are linked to a group of fatal neurodegenerative diseases called TDP-43 proteinopathies, which include amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD). Although our understanding of the physiological function of TDP-43 is rapidly advancing, the molecular mechanisms associated with its pathogenesis remain poorly understood. Accumulating evidence suggests that endoplasmic reticulum (ER) stress and the unfolded protein response (UPR) are important players in TDP-43 pathology. However, while neurons derived from autopsied ALS and FTLD patients revealed TDP-43 deposits in the ER and displayed UPR activation, data originated from in vitro and in vivo TDP-43 models produced contradictory results. In this review, we will explore the complex interplay between TDP-43 pathology, ER stress, and the UPR by breaking down the evidence available in the literature and addressing the reasons behind these discrepancies. We also highlight underexplored areas and key unanswered questions in the field. A better synchronization and integration of methodologies, models, and mechanistic pathways will be crucial to discover the true nature of the TDP-43 and ER stress relationship and, ultimately, to uncover the full therapeutic potential of the UPR.